The Development of Islamic Studies in the Early Islamic World in the Context of Legal Culture - Cinta Refalina Zalianti; Prity Aura Nadine; Wiwie Sapitri; Surya Sukti (Mir'ah: Family Law and Legal Culture, 2025)
This paper examines the values of the development of Islam during the early prophethood of the Prophet Muhammad by looking at it from the context of legal culture in the field of science that systematically studies various aspects of Islam ranging from the development of Islamic studies in the early days to the change of Islamic studies from Mosques to Madrasahs, this study aims to understand the meaning of the Islamic world, Islamic society, the development of Islamic studies in the early days, and the transition of Islamic studies. The research method in this article is through literature search by looking for relevant sources through journals / newspapers / websites. The results of research on the development of Islamic studies in the early days focused on monotheism, theory, and practice of the Qur'an and Hadith on worship and morals, reading, writing and arithmetic for the basic level, the content of the Qur'an, and the basics of religion for the advanced level. However, the development of Islamic studies initially in the Mosque at this time occurred because the legal culture of Indonesian society is very thick where madrasah is very identical to its position adjacent to the Mosque, Surau, or Musholla. This is intended as an effort to develop Islamic educational institutions, to respond to the high needs of the community to learn Islamic education, as well as to facilitate students with the presence of a mosque as a center of worship that is centrally positioned in 1 (one) complex.